Using Visual Trepan to Treat Single Segment Ossification of the Ligamentum Flavum Under Endoscopy. Issue 5 (29th October 2019) - Zhao, Wei; Yang, Sen; Diao, Wen‐bo; Yan, Ming; Wu, Wen‐jie; Luo, Fei
Abstract : This article describes the trepan technique for treating single segment ossification of the ligamentum flavum (OLF) using an endoscope. OLF is the most common cause of thoracic spinal stenosis. The most common surgical procedures involve semi‐lamina or full‐lamina resection and decompression. However, considering the anatomical structure of the thoracic spinal canal and the combination of OLF, traditional surgery has higher risks, more complications, and greater technical requirements. In the past ten years, with the development of endoscopic technology, spinal endoscopy has been increasingly applied for the treatment of intervertebral disc herniation and spinal canal stenosis. The present study demonstrated the effectiveness of visual trepan decompression under spinal endoscopy used for patients with single segment OLF. This surgical procedure had many advantages, including a shorter operation time, minimal trauma, less expenditure, and better functional recovery over the conventional open surgery.